Evaluation of through-thickness residual stresses in conventional and narrow grooved stainless steel welds. (August 2020) - Taraphdar, PK; Mahapatra, MM; Pradhan, AK; Singh, PK; Sharma, Kamal; Kumar, Suranjit
Thick AISI 304L stainless steel plates were welded using the gas metal arc welding process, and through-thickness residual stresses were evaluated by finite element simulation and the deep hole drilling technique. 3D moving heat source-based thermo-mechanical models were implemented to evaluate through-thickness residual stresses. The effects of the weld groove geometries and external restraints on the pattern of through-thickness residual stresses were studied. The maximum magnitude of locked-in residual stresses was recorded beneath the top surface, at a depth of around 6 mm. In comparison to conventional weld groove, the narrow weld groove configuration exhibited a 20–40% reduction in peak residual stresses. A significant rise in residual stresses was observed in constrained welds. The effect of the yield strength of the filler material on the evaluation of the through-thickness residual stress distribution in the course of finite element modeling was illustrated. The evolution of through-thickness residual stresses was also assessed concerning each weld pass.